Rethinking the Empty Ballot Box in Pilkada: Between Democratic Substance and Legal Formalism - Sultoni Fikri; Syofyan Hadi; Baharuddin Riqiey; Rizky Bangun Wibisono (Jurnal Suara Hukum, 2025)
The phenomenon of single-candidate elections in regional head elections (Pilkada) poses challenges to the democratic principles of directness, generality, freedom, confidentiality, honesty, and fairness. To address such electoral impasses, the "empty ballot box" mechanism was introduced through Constitutional Court Decision No. 100/PUU-XIII/2015 and supported by General Election Commission Regulations (PKPU), offering voters an alternative. However, this mechanism raises critical legal and democratic concerns—whether it truly reflects popular sovereignty or merely serves as an administrative formality. This study examines the legal legitimacy, democratic substance, and systemic consequences of the empty ballot box in Pilkada. Using a doctrinal legal methodology with statutory and conceptual approaches, the analysis reveals that the empty box mechanism predominantly acts as an administrative safeguard rather than a vehicle of the people's will. While it ensures procedural continuity, it fails to address the deeper issues of political representation and structural deficiencies in candidate nomination. The dominance of legal positivism in regulating this mechanism neglects principles of substantive justice and meaningful participation. This study argues for a comprehensive legal reform that moves beyond formal compliance and embraces progressive legal principles. Such reform should strengthen political party accountability, support independent candidacies, and expand public participation in candidate nomination. By reframing the empty box through the lens of democratic renewal and human rights, this article contributes a novel critique of electoral design in Indonesia.